2020
DOI: 10.2217/fvl-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dynamics of Varicella Incidence in Bulgaria

Abstract: Aim: Spatial and temporal distribution of varicella is heterogenic and insufficiently studied in Europe. The present study tries to fill the gap that exists about the seasonality of the infection in Bulgaria. Materials & methods: A 4-year retrospective study of the monthly and seasonal varicella epidemiology was performed at both national and district level. Results: In Bulgaria, varicella incidence peaked during winter (37% of the 2015–2018 cases), followed by spring (33%) and autumn (23%). Highly populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Both relative and absolute search query volumes for varicella keywords during the 5 years preceding the COVID-19 pandemic displayed seasonal variation in countries without UVV, peaking in the autumn or winter and in the spring. This pattern aligns with seasonal variation reported in studies of incident varicella infections and varicella-related hospitalizations from several European countries [1,19,[23][24][25][26][27][28][29]. Using data from Bulgaria as a comparator, we quantitatively evaluated clinical varicella incidence with the Google Trends Index, finding an adjusted R 2 value of 0.75.…”
Section: Plos Onesupporting
confidence: 76%
“…Both relative and absolute search query volumes for varicella keywords during the 5 years preceding the COVID-19 pandemic displayed seasonal variation in countries without UVV, peaking in the autumn or winter and in the spring. This pattern aligns with seasonal variation reported in studies of incident varicella infections and varicella-related hospitalizations from several European countries [1,19,[23][24][25][26][27][28][29]. Using data from Bulgaria as a comparator, we quantitatively evaluated clinical varicella incidence with the Google Trends Index, finding an adjusted R 2 value of 0.75.…”
Section: Plos Onesupporting
confidence: 76%
“…26,27 In tropical climates, chickenpox has a more distinct seasonal patternwith cases occurring in spring and winter -compared to temperate climates where cases occur throughout the year with lowest case counts during summer months. 24,[28][29][30][31] Across all climatic zones, temperature and rainfall contribute to the seasonality of disease. 32,33 A modelling study of chickenpox dynamics in Mallorca, a Mediterranean island, found that solar radiation and water vapor pressure were climatic drivers of chickenpox seasonality, with peaks in case numbers in June.…”
Section: Seasonality and Climatic Drivers Of Chickenpoxmentioning
confidence: 99%
“…While cases tend to be inversely related with temperature, even in temperate climate zones, consistent caseloads throughout the year are more commonly experience in temperate climate zones relative to tropical zones. [29][30][31] In contrast to the Elliniko outbreak, the larger of two outbreaks in Malakasa camp and the outbreak in Raidestos reflect expected seasonality of chickenpox, with higher incidence of cases in cooler seasons. Specifically, the larger of two outbreaks in Malakasa camp occurred from December 2016 -May 2017, with case counts staying consistently lower after February 2017.…”
Section: Seasonalitymentioning
confidence: 99%